Young Schema Questionnaire-Short Form : validación en Colombia (2012)
ABSTRACT: The aim of this study was to assess the factor structure of the Young Schema Questionnaire-Short Form ([YSQ-SF], Young, 1999) and the gender differences in early maladaptive schemas. The study took place in Colombia, where 1392 university students (541 male y 851 female) completed the YSQ-SF. The results confirmed the existence of the original 15 first-order factors, in consistency with the 15 theoretical schemas. However, the results for the second-order structure were less conclusive, as both a three second order factor and a five second order factor structures showed similar fit indices. Alpha coefficients for the schemas rated between 0.74 and 0.89. Men scored higher than women on several schemas.